Chains as strong as the weakest link: remote assessment of aquatic resource use on spring migration by Bewick's Swans - Rascha J. M. Nuijten; Bart A. Nolet (Resilience Alliance, 2020)
Migratory species are threatened worldwide by climate change, overexploitation, and habitat changes. Availability of suitable habitat is important for flying migrants, and in particular for large birds that use the energetically expensive flapping flight mode, such as the Bewick's Swan (Cygnus columbianus bewickii). Bewick's Swans largely feed on aquatic macrophytes during migration that may disappear when nutrient levels, waves, and turbidity exceed certain thresholds. Macrophyte collapse has been suggested as a reason for the sharp decline of the Bewick's Swan population during 1995-2015. We used Bewick's Swans fitted with GPS/GSM neck collars including an accelerometer and water sensor to record the occurrence of aquatic foraging in remote stopovers along their migratory route. We concentrated on spring migration, when stopovers are longer than during autumn, and focused on four key sites identified in earlier tracking studies. Within these sites, we identified areas that are protected based on the World Database on Protected Areas (WDPA). During three years (2017-2019), we obtained a total of 51 complete spring tracks of adult female Bewick's Swans. Most swans showed aquatic foraging along the coast of Estonia and in Dvina Bay, and about half in the Gulf of Finland and Cheskaya Bay. In Estonia and in the Gulf of Finland, swans predominantly used protected zones, but in Dvina Bay swans also foraged extensively in areas that are currently not protected according to WDPA. No protected areas occur in Cheskaya Bay. Macrophyte vegetation is threatened by ongoing or planned construction works in the Gulf of Finland and Dvina Bay, and by future oil and gas exploitation in Cheskaya Bay. Our study shows how migrants can be used as sentinels to pinpoint areas that require protection in order to maintain a chain of suitable stopovers on their migration.